2013
DOI: 10.1111/agec.12006
|View full text |Cite
|
Sign up to set email alerts
|

Which farmers benefit the most from Bt corn adoption? Estimating heterogeneity effects in the Philippines

Abstract: The potential contributions of new biotechnologies to sustainable food and income security have been the subject of widespread discussions around the turn of the 21st century. But distributional issues of which segments of adopters of genetically modified (GM) crops benefit the most have not been given ample attention). Using propensity scores, we apply the (a) stratification-multilevel method of estimating heterogeneous treatment effects; and the (b) matching-smoothing method of estimating heterogeneous treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Third, we analyze how the estimated income and poverty effects of cooperative membership differ across farmers. We apply methods 5 proposed by Abebaw and Haile (2013), Bernard et al (2008), and Mutuc et al (2013). We calculate the average treatment effect on the treated (ATT), which measures the impact of cooperative membership on farm income and poverty for actual cooperative members only:…”
Section: Propensity Score Matchingmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we analyze how the estimated income and poverty effects of cooperative membership differ across farmers. We apply methods 5 proposed by Abebaw and Haile (2013), Bernard et al (2008), and Mutuc et al (2013). We calculate the average treatment effect on the treated (ATT), which measures the impact of cooperative membership on farm income and poverty for actual cooperative members only:…”
Section: Propensity Score Matchingmentioning
confidence: 99%
“…. Our method, inspired byAbebaw and Haile (2013),Bernard et al (2008) andMutuc et al (2013) has the advantage that non-linearities can be revealed by looking at the whole distribution of the treatment effects.…”
mentioning
confidence: 99%
“…At the farm level, the distributional impacts studied concerned mainly how adoption and economic benefits are distributed among farmers in different income groups or, more rarely, in relation to gender. Mutuc et al [61] presented results from the Philippines showing that poorer farmers without access to irrigation and living further away from formal seed suppliers are less inclined to adopt Bt maize. However, in another study from the Philippines, Sanglestsawai et al [62] showed that if they can adopt Bt maize, lower-yielding farmers, who also tend to be the poorest, experience higher yield increases than farmers with higher yields before Bt maize adoption.…”
Section: How Are Different Social Impacts Addressed?mentioning
confidence: 99%
“…In EA, China reached a 90% adoption rate in 1992 (Morris 1998), and many SEA countries are catching up since 1990 ( Figure 3). In the Philippines, Bt-maize varieties have also been spreading, from 1% in 2002 to 13% in and 19% in 2009(Mutuc et al 2013. As is shown below, maize is increasingly becoming an important source of fodders for the growing livestock sector in SEA.…”
Section: Improved Varietiesmentioning
confidence: 99%